Limited Economic-Ecological Trade-Offs in a Shifting Agricultural Landscape: A Case Study From Kern County, California - Wartenberg, Ariani C.; Moanga, Diana; Potts, Matthew D.; Butsic, Van (Frontiers in Sustainable Food Systems, 2021)
Increasing global food production and livelihoods while maintaining ecosystem health will require significant changes in the way existing farming landscapes are managed. To this end, developing a systemic understanding of the economic and ecological impacts of different cropping systems, and identifying trade-offs and synergies between them, is crucial to inform decision-making for policy makers and landowners. Here, we investigate the impacts of agricultural land-use change for 15 distinct crops in Kern County, California, by looking at spatial and temporal changes in ecosystem indicators. We focus our analysis on three agricultural ecosystem pressures (water use, soil erosion, and pesticide use) and three agricultural ecosystem services (profits, calorie production, and C sequestration). Between 2002 and 2018, agriculture in Kern County underwent a shift from annual row crop to nut tree crop production. At the landscape-scale, we found high increases in ecosystem service provision (total profits, calorie production, and annual C sequestration increased by 105, 29, and 37%, respectively), coupled with smaller changes in ecosystem pressures (total soil erosion and evapotranspiration increased by 10 and 5%, respectively, and total pesticide use declined by 4%). We identified no salient trade-offs or synergies among crops. Our results illustrate that in the highly productive agricultural hotspot of Kern County, a combination of changes in land-cover allocation or land-use efficiency may have mitigated stronger negative environmental impacts following a broad shift from annual to perennial crops.